Antegrade CT pyelography of right retrocaval ureter causing ureteral stenosis and ureterohydronephrosis in an exotic shorthair cat: A case report - Zhang, Bowen; Fu, Mengzhu; Zhang, Di; Jin, Yipeng; Liu, Gang (Frontiers in Veterinary Science, 2023)
Retrocaval ureter is a rarely reported congenital malformation of the caudal vena cava in veterinary medicine. In this report, a 2-year-old exotic shorthair cat weighing 3.4 kg was presented for depression and loss of appetite. Laboratory findings was unremarkable. Abdominal radiography revealed right renomegaly, and ultrasonography suggested right ureterohydronephrosis. Right retrocaval ureter was recognized by computed tomography. An antegrade pyelography was performed to identify the localization of obstruction and whether obstruction was complete or partial. Complete right ureteral stenosis was confirmed through right antegrade pyelography on computed tomography. The cat underwent right nephroureteroectomy and recovered well after surgery. This is the first report of successful diagnosis and treatment of retrocaval ureter in a cat with significant clinical and imaging signs, using ultrasonographically guided percutaneous antegrade pyelography and multimodal imaging such as radiography, ultrasonography, and computed tomography.